Tecnologias no trabalho dos profissionais de enfermagem em Serviços de Atenção Domiciliar - Bruna Dias França (2021)
Introduction: This study was based on the premise that the concept of technology has been used emphatically in everyday life, wrongly, as it has usually been understood only as a product, a machine. It is noticed that this conceptual misunderstanding prevents the recognition of technologies, innovations and daily creations of nursing during their work process in home care. Therefore, the aim of this study was to analyze the use of technologies in the work process of nursing professionals in the Home Care Service. Method: qualitative study, anchored in the theoretical-methodological framework of Marxist dialectics. The data production was set in the home care services of the Unified Health System in the municipalities: Belo Horizonte, Contagem and Pará de Minas, in Minas Gerais, and took place through interviews guided by a semi-structured script, with nurses and nursing technicians from the Home Care Service. Data were submitted to Critical Discourse Analysis, from the perspective of Fairclough, enabling the discussion of two empirical categories: nursing work in home care; and technologies in nursing work in home care: from conceptions to improvisations. Results: indicated that nurses and nursing technicians assume organizational, care and educational/relational activities. And in certain situations, these workers are encouraged to adapt and innovate to achieve the goal of care. This is especially due to the live work in action, which is based on the needs of the work and encourages the minds of workers to think of solutions for the unique situations of home care. Among the identified technologies, technologies commonly used in the health field are presented, but innovative and specific technologies for the Home Care Service are also evidenced, such as: route elaboration and coordination; visit schedule management; eligibility classification for admission to the Home Care Service; case discussion in person or by WhatsApp; assembly of a suitcase with materials needed for home visits. It is also identified the need for monitoring and evaluation of the technologies implemented during patient care, to ensure quality care. Conclusion: care, management and educational technologies used in the work process of the nursing team in the Home Care Service were evidenced. It was identified that nurses and nursing technicians assume organizational, care and educational/relational activities. In certain situations, these workers are encouraged to adapt and innovate to reach their goal.